KECEPATAN KESEMBUHAN KEPUTIHAN PATOLOGIS DENGAN INTERVENSI REBUSAN DAUN SIRIH - Supratiknyo Supratiknyo (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2015)
One of the problems of reproductive health is a pathological vaginal discharge, which caused by an infection or poor personal hygiene. Betel leaf is one of the herbal remedies that can cure the pathological vaginal discharge because antibiotic of betel leaf contain substances that can kill and protect the vagina from bacteria and viruses. The purpose of this study was to determine the speed of healing pathological vaginal discharge with betel leaf stew intervention in young women aged 18-21 years in Ma'had Aly Dormitory of Sukorejo Situbondo. This study used observation, the population in this experiment are all young women aged 18-21 years who have pathological vaginal discharge. Sampling technique in this research is total sampling with 22 respondents. Respondents who received the decoction intervention of 15 pieces of betel leaf. Eight teenage girls did not have difference speed of healing after given intervention. Furthermore, the data were analyzed using a test